Hb Guangxi [β65(E9)Lys→Glu (AAG>GAG); HBB: c.196A>G]: A Novel β-Globin Variant. (2nd November 2021) - Xu, Miao; Chen, Wei-Dong; Wang, Ya-Jun; Zhou, Yu; Li, Jie; Xu, An-Ping; Ji, Ling
Abstract: We report a novel variant found in a female from Guilin municipality in the Guangxi Zhuang Autonomous Region of the People's Republic of China. This variant can be readily detected by both cation exchange high performance liquid chromatography (HPLC) and capillary electrophoresis (CE). Sanger sequencing revealed a novel mutation on the β-globin gene [β65(E9)Lys→Glu ( A AG> G AG); HBB : c.196A>G]. We named this novel hemoglobin (Hb) variant Hb Guangxi for the place of origin of the proband.